Analisis Rasio Likuiditas dan Rasio Solvabilitas pada PT. Bank Rakyat Indonesia (Persero) Tbk. yang Terdaftar di Bursa Efek Indonesia - Hanafi, Muh. Alam Nasyrah; Burhami, Abdul Hafid; Aqila (STKIP MAJENANG, 2025)
This study aims to analyze the use of Liquidity Ratio and Solvency Ratio in measuring the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk during the period 2019 to 2023. The method used is quantitative analysis with secondary data sources and data collection techniques through documentation. Data analysis was carried out using Liquidity Ratio and Solvency Ratio. The results of the study show that the level of Liquidity Ratio in the period 2019–2023 indicates the company's ability to meet its short-term obligations, which places BRI's financial performance in the good category. In addition, the level of Solvency Ratio in the same period shows that BRI is able to meet its long-term obligations, reflecting solid solvency and good financial performance.